Gas drying with ionic liquids. Issue 2 (29th August 2017) - Han, Jingli; Dai, Chengna; Lei, Zhigang; Chen, Biaohua
Abstract : The gas drying technology with ionic liquids (ILs) was systematically studied ranging from the molecular level to industrial scale. The COSMO‐RS model was first used to screen the suitable IL and provide theoretical insights at the molecular level. Toward CO2 gas dehydration, we measured the CO2 solubility in single [EMIM][Tf2 N] and in the [EMIM][Tf2 N] + H2 O mixture, as well as the vapor‐liquid equilibrium (VLE) of [EMIM][Tf2 N] + H2 O system, to justify the applicability of UNIFAC model. Based on the thermodynamic study, the rigorous equilibrium (EQ) stage mathematical model was established for process simulation. The gas drying experiment with IL was also performed and the water content in gas product can be reduced to 375 ppm. It was confirmed that a less flow rate of absorbent, a higher CO2 recovery ratio and a much lower energy consumption can be achieved with IL than with the conventional triethylene glycol (TEG). © 2017 American Institute of Chemical Engineers AIChE J, 64: 606–619, 2018